Ultrasensitive Multiparameter Phenotyping of Rare Cells Using an Integrated Digital‐Molecular‐Counting Microfluidic Well Plate. Issue 31 (25th June 2021) - Su, Shiuan‐Haur; Song, Yujing; Newstead, Michael W.; Cai, Tao; Wu, MengXi; Stephens, Andrew; Singer, Benjamin H.; Kurabayashi, Katsuo
Abstract: Integrated microfluidic cellular phenotyping platforms provide a promising means of studying a variety of inflammatory diseases mediated by cell‐secreted cytokines. However, immunosensors integrated in previous microfluidic platforms lack the sensitivity to detect small signals in the cellular secretion of proinflammatory cytokines with high precision. This limitation prohibits researchers from studying cells secreting cytokines at low abundance or existing at a small population. Herein, the authors present an integrated platform named the "digital Phenoplate (dPP), " which integrates digital immunosensors into a microfluidic chip with on‐chip cell assay chambers, and demonstrates ultrasensitive cellular cytokine secretory profile measurement. The integrated sensors yield a limit of detection as small as 0.25 pg mL −1 for mouse tumor necrosis factor alpha (TNF‐α). Each on‐chip cell assay chamber confines cells whose population ranges from ≈20 to 600 in arrayed single‐cell trapping microwells. Together, these microfluidic features of the dPP simultaneously permit precise counting and image‐based cytometry of individual cells while performing parallel measurements of TNF‐α released from rare cells under multiple stimulant conditions for multiple samples. The dPP platform is broadly applicable to the characterization of cellular phenotypes demanding high precision and high throughput. Abstract : This study develops a cellular phenotyping platform for cell trapping/culture, digital‐molecular‐counting immunosensing, and image‐based cytometry on a single microfluidic chip. The platform enables ultrasensitive cytokine detection and multiparametric phenotyping of multiple rare cell samples. It is extensively applied on studying primary microglia's functional phenotypic differences between amyloid‐expressing Alzheimer's disease model mice and wild‐type mice.